Seed dispersal pattens of large-seeded trees in the forests of Singapore - See, James Zhe Yuan (Nanyang Technological University, 2024)
Seed dispersal is integral for the continued persistence of trees, as successful dispersal reduces competition for seedlings and allows for greater access to resources like space, light, and nutrients. However, for large-seeded animal-dispersed trees in environments that have lost their large animal dispersers (megafauna), their underlying dispersal mechanisms and the extent of their dispersal are not entirely clear. A possible explanation is that these large seeds are dispersed through secondary dispersal, where smaller animals move these seeds after they have fallen to the ground. To test if large-seeded trees are being dispersed in Singapore, which has no megafauna left, recruitment rates and spatial distribution of selected tree species in two forest plots in Bukit Timah Nature Reserve were calculated. The viability of secondary seed dispersal by smaller animals was then tested with a field experiment where large seeds were deployed in two forest locations. The results suggest that common large-seeded trees are successfully recruiting (producing offspring) but they and smaller-seeded trees are not dispersed well, although smaller animals can be seen to be moving placed seeds. The results could provide insights on how similarly defaunated tropical forests are adapting to these changes.